Evaluation of Lubricating Oil Preparation Procedures for the Determination of Al, Ba, Mo, Si and V by High-Resolution Continuum Source FAAS - Amorim Filho, Volnei Resta [UNESP]; Gomes Neto, José Anchieta [UNESP] (Japan Soc Analytical Chemistry, 2009)
Microwave-assisted acid decomposition and oil-in-water emulsification were evaluated as sample pretreatment procedures to determine Al, Ba, Mo, Si and V in lubricating oils by high-resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS). Average recoveries of Al, Ba and V in oil digests (107, 103 and 101%) were close to those obtained for emulsions prepared in kerosene medium (94, 113 and 95%). Average recoveries for Mo were close to 105 and 46% for emulsions and digests, respectively. Improved average recoveries (101%) were obtained for Mo in digests using the analyte addition technique. Silicon was successfully quantified only in digested samples. Limits of quantification for Al. Ba, Mo and V were 1.4, 31.5, 1.5 and 11.4-fold lower than those obtained by line-source FAAS. Enhanced sensitivity, multi-elemental capability, and high sample throughput are among the main advantages of HR-CS FAAS in comparison with the line-source FAAS technique.